Changes in the Situation of Different Demographic Groups in the Lithuanian Labour Market and the Influence of Methodical Differences on Relative Unemployment Indicators - Pocius, Arūnas (Lithuanian Journal of Statistics, 2016)
The paper analyses employment, activity and unemployment trends in Lithuania by sex and age, with thefocus on the monitoring of the labour market situation of different demographic groups. The possibilities of integratingwomen and men, elderly and young people into the labour market are evaluated using key labour market indicators. Differentunemployment estimation methods are used for the assessment of changes in the labour market situation of differentdemographic groups in Lithuania. Statistical data analysis is supplemented by the results of individual research.
Keywords: employment rate; unemployment rate; activity of the population; labour market; labour market policy; long-term unemployment; integration